Los Castillos ante el tribunal de la Inquisición de Cuenca (siglos xv-xvii) - Vincent Parello (Les Cahiers de Framespa)
Before the 15th-17th centuries, the members of the Castillo family, of well-known convert descent, were persecuted by the Holy office for political and social reasons rather than religious ones. For more than two centuries, the Castillos played a significant role in the entourage of the Marquis of Villena, which led to grudges and jealousies from the part of old-Christian labourers and hidalgos.